KOMBINASI CAESAR CIPHER DAN REVERSE CIPHER BERDASARKAN CIPHER BLOCK CHAINING - Najah, Maulidyah Lailatun; Santoso, Kiswara Agung (Jurusan Matematika FMIPA Universitas Jember, 2021)
Communication in the current era of globalization is very developed. Many applications that can be used to facilitate communication. However, because of this convenience, the security of the information contained in it will be more easily hacked by irresponsible people. Cryptography is the science or art for security message. In cryptography there are two important processes, namely encryption and decryption. The sender's job is to encrypt the message and the receiver's job is to decrypt the message. The key used for this cryptographic process is the Cipher Block Chaining (CBC) operation mode. CBC mode is a very simple operation mode, so additional techniques are needed to make it more secure. The plaintext will be replaced with new plaintext resulting from a combination of Caesar Cipher and Reverse Cipher techniques. The results obtained indicate that the application of plaintext modifications to CBC can improve message security because the keys used are increasingly complex.